Risk factors for early surgical intervention in neonates with gastroesophageal reflux disease - Shady S Shokry; Khaled M El-Asmar; Mohamed M Dahab; Tarek A Hassan (EL-Med-Pub, 2022)
Background: Surgical intervention in neonates with Gastro-esophageal Reflux Disease (GERD) is usually reserved for failure of medical management or those having life-threatening complications of GERD. The optimal timing of intervention is still debatable.  We aimed to identify the high-risk neonates with GERD requiring early surgical intervention. Methods: This prospective cohort study was conducted at NICU and Pediatric Surgery Department, Ain Shams University, from June 2017 to June 2020, and enrolled the neonates and infants below 2 months with symptoms and signs suggestive of GERD. Demographic data, clinical history, medical management, need for antireflux surgery, and outcomes were recorded. Results: In this study, 40 patients were enrolled and all were started on medical treatment. After the failure of medical management or life-threatening complications, 12 of these underwent anti-reflux surgery. In the medical group, six patients suffered from major complications (bronchopulmonary dysplasia and sepsis) and four mortalities. In the surgical group, three mortalities related to the development of bronchopulmonary dysplasia due to prolonged ventilation prior to surgery were recorded. The need for surgical intervention was significantly associated with younger gestational age (p = 0.001), younger age at presentation (p = 0.006), and lower weight at presentation (p = 0.034). Conclusion: Medical treatment of more than 35 days with unsatisfactory response, low birth weight, gestational age (≤32 weeks), and NICU admission in the first 10 days of life are considered high-risk factors for early anti-reflux surgery in neonates.